Low-floating-fiber rigid-tough balanced polyformaldehyde composite material and preparation method thereof

By adding sodium sulfonate to modify silicate, polyurethane elastomer and alkali-free glass fiber to the polyformaldehyde material, combined with the extrusion granulation process, the low impact toughness and floating fiber problems of polyformaldehyde material are solved, achieving high The preparation of low-floating fiber rigid and tough balanced polyformaldehyde composite materials improves the flame retardant and mechanical properties of the materials.

CN119286188APending Publication Date: 2025-01-10江苏尚艾新材料科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411549928.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Polyformaldehyde materials are prone to crystallization during molding, resulting in low impact toughness and high notch sensitivity. The existing toughening modification methods will reduce strength and modulus, and glass fiber reinforcement will lead to floating fiber problems, affecting appearance and application.

Method used

Low-floating fiber rigid and tough balanced polyformaldehyde composite material is adopted, including 50-90 parts by weight of polyformaldehyde, 8-15 parts by weight of sodium sulfonate modified silicate, 5-20 parts by weight of polyurethane elastomer, 10-30 parts by weight of Parts of alkali-free glass fiber, 10-30 parts by weight of mineral powder, 1-5 parts by weight of diphenylmethane diisocyanate compatibility, 0.1-0.5 parts by weight of antioxidant and 0.1-0.4 parts by weight of stear Zinc acid lubricant is prepared by extrusion granulation process, and combined with sodium sulfonate to modify the flame retardant effect of silicate.

Benefits of technology

The flame retardant and mechanical properties of the material are improved, the floating fiber problem is reduced, the toughness and strength of the material are improved, the preparation process is simplified, and the continuous production is suitable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005114798260000101
    Figure BDA0005114798260000101
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and discloses a low-floating-fiber rigid-tough balanced polyformaldehyde composite material and a preparation method thereof.The low-floating-fiber rigid-tough balanced polyformaldehyde composite material is prepared from polyformaldehyde, sodium sulfonate modified silicate ester, a polyurethane elastomer, mineral powder, a diphenylmethane diisocyanate compatilizer, an antioxidant 1010 and a zinc stearate lubricant; sequentially adding the raw materials into a high-speed mixer, stirring to obtain a mixed material, putting the premix into a feeding hopper of a double-screw extruder, feeding alkali-free glass fibers from the fifth section side, and carrying out melt extrusion to obtain the molten low-floating-fiber rigid-tough balanced polyformaldehyde composite material. And drawing, water-cooling, blow-drying, pelletizing and collecting to finally obtain the solid granular low-floating-fiber rigid-tough balanced polyformaldehyde composite material. The silicon element, the nitrogen element and the sodium sulfonate group in the sodium sulfonate modified silicate ester have good flame retardant effect, and the synergistic flame retardant effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a low-floating fiber-rigidity-balanced polyoxymethylene composite material and a preparation method thereof. Background Art

[0002] Polyoxymethylene (POM) is a linear polymer with no side chains, high density, and high crystallinity. It has good physical, mechanical and chemical properties, especially excellent friction resistance. POM is also one of the five major engineering plastics, commonly known as Saigang, which can replace some metal materials and can be used in automobiles, textile accessories, electronic appliances, precision machinery and other fields.

[0003] Polyoxymethylene material is an engineering plastic with good comprehensive performance. It is easy to crystallize during molding and processing, and has high crystallization degree and fast crystallization speed, forming large radioactive spherulites, resulting in low impact toughness and high notch sensitivity of the material, which limits its application to a certain extent. The invention patent with publication number CN201010280691.7 discloses a toughened polyoxymethylene blended modified material and its preparation method. Although toughening can improve the impact resistance of the material, it will also lead to a decrease in strength and modulus; the invention patent with publication number CN200710077042.5 discloses a reinforced and toughened polyoxymethylene composition and its preparation method. While toughening, it is reinforced with glass fiber, which has a certain effect of balancing rigidity and toughness. However, with the addition of glass fiber, floating fibers will appear on the surface of the product, resulting in poor appearance and increased scrap rate, which limits the application of the modified polyoxymethylene composite material.

[0004] Therefore, with the increasing application of polyoxymethylene materials, higher requirements are placed on the comprehensive performance of polyoxymethylene. Modified polyoxymethylene is required not only to take into account both rigidity and toughness, but also to consider the impact on the appearance of the product during actual use. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the deficiencies in the prior art, the present invention provides a low-floating fiber, rigidity-toughness balanced polyoxymethylene composite material and a preparation method thereof, which has good flame retardancy and mechanical properties.

[0007] (II) Technical solution

[0008] To achieve the above object, the present invention provides the following technical scheme: a low-floating fiber rigid-toughness balanced polyoxymethylene composite material, comprising the following weight components: 50-90 weight parts of polyoxymethylene, 8-15 weight parts of sodium sulfonate modified silicate, 5-20 weight parts of polyurethane elastomer, 10-30 weight parts of alkali-free glass fiber, 10-30 weight parts of mineral powder, 1-5 weight parts of diphenylmethane diisocyanate compatibilizer, 0.1-0.5 weight parts of antioxidant 1010, and 0.1-0.4 weight parts of zinc stearate lubricant;

[0009] The polyoxymethylene is copolymerized oxymethylene, preferably copolymerized oxymethylene with medium viscosity and a melt flow rate of about 10 g / 10 min;

[0010] The polyurethane elastomer is a polyester polyurethane or a polyether polyurethane or a composite of the two, with a Shore A hardness of 80-90 and a density of 1.19 g / cm3;

[0011] The alkali-free glass fiber is an alkali-free chopped glass fiber, preferably with a fiber length of 3.0-5.0 mm, a diameter of 10-15 μm, and an alkali-free chopped glass fiber treated with a coupling agent on the surface;

[0012] The mineral powder is one or a combination of talcum powder, glass micro beads or crushed glass fiber powder, and the mineral powder is 2000-3000 mesh mineral powder.

[0013] Preferably, the preparation method of the sodium sulfonate modified silicate is:

[0014] (1) Add pentaerythritol methyl silicate and propyl caprolactone to N,N-dimethylformamide solvent, mix well, add sodium hydroxide catalyst, react at 60-70° C. for 7-10 hours, and after the reaction, distill under reduced pressure, wash, and dry to obtain intermediate 1;

[0015] (2) Add intermediate 1 and 2-methylene succinic anhydride to the reactor, stir evenly, continue to add 4-dimethylaminopyridine catalyst, control the temperature between 50-80° C., react for 1.5-4 hours, filter, wash and dry after completion to obtain intermediate 2;

[0016] (3) adding intermediate 2 to toluene solvent, stirring and dispersing, then adding 4-dimethylaminophenol and p-toluenesulfonic acid catalyst, heating to 105-115° C., reacting for 7-10 hours, and after the reaction is completed, distilling under reduced pressure to obtain intermediate 3;

[0017] (4) The intermediate 3 and 1,3-propane sultone are dissolved in a 1,4-dioxane solvent, and then a sodium hydroxide solution with a mass fraction of 3-5% is added dropwise, and the temperature is raised to 60-85° C. for reaction. After the reaction, the solvent is removed by concentration under reduced pressure, and the crude product is recrystallized in ethanol to obtain a sodium sulfonate modified silicate.

[0018] Preferably, the mass ratio of pentaerythritol methyl silicate, propyl caprolactone and sodium hydroxide catalyst in (1) is 1:1.2-1.4:0.02-0.03.

[0019] Preferably, the mass ratio of the intermediate 1, 2-methylenesuccinic anhydride, and 4-dimethylaminopyridine catalyst in (2) is 1.3-1.5:1:0.01-0.02.

[0020] Preferably, the mass ratio of the intermediate 2,4-dimethylaminophenol to the p-toluenesulfonic acid catalyst in (3) is 1.1-1.4:1:0.02-0.04.

[0021] Preferably, the mass ratio of the intermediate 3 to 1,3-propane sultone in (4) is 1:2.1-2.3.

[0022] Preferably, the reaction time in (4) is 6-10 h.

[0023] Preferably, the preparation method of the low-floating fiber-rigidity-balanced polyoxymethylene composite material is:

[0024] S1, adding polyoxymethylene, sodium sulfonate modified silicate, polyurethane elastomer, mineral powder, diphenylmethane diisocyanate compatibilizer, antioxidant 1010, and zinc stearate lubricant into a high-speed mixer in sequence, stirring for 5-10 minutes to obtain a mixture;

[0025] S2, extrusion granulation: put the premix in S1 into the feeding hopper of the twin-screw extruder, add alkali-free glass fiber from the side feed of the fifth section, and perform melt extrusion to obtain a molten low-floating fiber rigidity and toughness balanced polyoxymethylene composite material; then after traction, water cooling, blow drying, pelletizing and collection, finally obtain a solid granular low-floating fiber rigidity and toughness balanced polyoxymethylene composite material; wherein the extruder is a co-rotating meshing twin-screw extruder, and the aspect ratio is between 40:1-50:1, and the temperature control of each zone of the extruder is: 150-180℃ for zones 1 to 3, 180-190℃ for zones 4 to 10, 190-195℃ for the head, 300-500rpm for the main engine speed, 10-30rpm for the main feeding frequency, 5-10rpm for the side feeding frequency, and -0.08-0MPa for the vacuum degree. (III) Beneficial technical effects

[0026] The invention provides a method for preparing a premixed material by sequentially adding polyoxymethylene, sodium sulfonate modified silicate, polyurethane elastomer, mineral powder, diphenylmethane diisocyanate compatibilizer, antioxidant 1010 and zinc stearate lubricant into a high-speed mixer, stirring the premixed material to obtain a premixed material, feeding the premixed material into a feeding hopper of a twin-screw extruder, feeding alkali-free glass fiber into the hopper from the fifth section, and performing melt extrusion to obtain a molten low-floating fiber rigidity-toughness balanced polyoxymethylene composite material; and finally obtaining a solid granular low-floating fiber rigidity-toughness balanced polyoxymethylene composite material through traction, water cooling, drying, pelletizing and collection.

[0027] The invention adopts the method of adding a compatibilizer to improve the compatibility of the polyurethane elastomer and the polyoxymethylene matrix, and improves the toughness of the material; the invention adopts mineral fiber composite filling reinforcement, which not only makes up for the reduction of strength and modulus of polyoxymethylene due to toughening, but also improves the floating fiber situation caused by glass fiber reinforcement; the preparation method of the invention has fewer steps, simple process, and can realize continuous production. The silicon element, nitrogen element, and sodium sulfonate group in the sodium sulfonate modified silicate all have good flame retardant effect, and synergistic flame retardant; and the intermediate 1 reacts with 2-methylene succinic anhydride to increase the substitution degree of the silicon element, so that its flame retardant effect is better. DETAILED DESCRIPTION

[0028] Example 1

[0029] A low-floating fiber rigid-toughness balanced polyoxymethylene composite material comprises the following weight components: 50 weight parts of polyoxymethylene, 8 weight parts of sodium sulfonate modified silicate, 5 weight parts of polyurethane elastomer, 10 weight parts of alkali-free glass fiber, 10 weight parts of mineral powder, 1 weight part of diphenylmethane diisocyanate compatibilizer, 0.1 weight part of antioxidant 1010, and 0.1 weight part of zinc stearate lubricant;

[0030] The polyoxymethylene is copolymerized oxymethylene, preferably copolymerized oxymethylene with medium viscosity and a melt flow rate of about 10 g / 10 min;

[0031] The polyurethane elastomer is a polyester polyurethane with a Shore A hardness of 80 and a density of 1.19 g / cm3;

[0032] The alkali-free glass fiber is an alkali-free chopped glass fiber, preferably with a fiber length of 3.0 mm, a diameter of 10 μm, and an alkali-free chopped glass fiber treated with a coupling agent on the surface;

[0033] The mineral powder is talcum powder, and the mineral powder is 2000 mesh mineral powder.

[0034] The preparation method of the sodium sulfonate modified silicate is:

[0035] (1) Add pentaerythritol methyl silicate and propyl hexyl lactone to N,N-dimethylformamide solvent, mix well, add sodium hydroxide catalyst, wherein the mass ratio of pentaerythritol methyl silicate, propyl hexyl lactone and sodium hydroxide catalyst is 1:1.2:0.02, react at 60°C for 7h, and after the reaction, distill under reduced pressure, wash and dry to obtain intermediate 1;

[0036] (2) adding intermediate 1 and 2-methylene succinic anhydride to the reactor, stirring evenly, and continuing to add 4-dimethylaminopyridine catalyst, wherein the mass ratio of intermediate 1, 2-methylene succinic anhydride and 4-dimethylaminopyridine catalyst is 1.3:1:0.01, controlling the temperature between 50°C, reacting for 1.5h, filtering after completion, washing and drying to obtain intermediate 2;

[0037] (3) adding intermediate 2 to toluene solvent, stirring and dispersing, and then adding 4-dimethylaminophenol and p-toluenesulfonic acid catalyst thereto, wherein the mass ratio of intermediate 2, 4-dimethylaminophenol, and p-toluenesulfonic acid catalyst is 1.4:1:0.04, heating to 115° C., reacting for 10 hours, and after the reaction is completed, distilling under reduced pressure to obtain intermediate 3;

[0038] (4) dissolving the intermediate 3 and 1,3-propane sultone in a 1,4-dioxane solvent, wherein the mass ratio of the intermediate 3 to 1,3-propane sultone is 1:2.3, then dropping a 5% sodium hydroxide solution, heating to 85° C. to react for 10 h, and after the reaction, concentrating under reduced pressure to remove the solvent, and the crude product is recrystallized in ethanol to obtain a sodium sulfonate modified silicate;

[0039] (5) adding polyoxymethylene, sodium sulfonate modified silicate, polyurethane elastomer, mineral powder, diphenylmethane diisocyanate compatibilizer, antioxidant 1010, and zinc stearate lubricant into a high-speed mixer in sequence, stirring for 10 minutes to obtain a mixture;

[0040] (6) Extrusion granulation: The premix in S1 is fed into the feed hopper of a twin-screw extruder, and alkali-free glass fiber is added from the side feed of the fifth section for melt extrusion to obtain a molten low-floating fiber, rigidity and toughness balanced polyoxymethylene composite material; after traction, water cooling, blow drying, pelletizing and collection, a solid granular low-floating fiber, rigidity and toughness balanced polyoxymethylene composite material is finally obtained; wherein the extruder is a co-rotating meshing twin-screw extruder with a length-to-diameter ratio of 40:1:1, and the temperature control of each zone of the extruder is: 150°C for zones 1 to 3, 180°C for zones 4 to 10, 190°C for the head, 300rpm for the main engine speed, 10rpm for the main feeding frequency, 5rpm for the side feeding frequency, and -0.08MPa for the vacuum degree.

[0041] Example 2

[0042] A low-floating fiber rigid-toughness balanced polyoxymethylene composite material comprises the following weight components: 90 weight parts of polyoxymethylene, 15 weight parts of sodium sulfonate modified silicate, 20 weight parts of polyurethane elastomer, 30 weight parts of alkali-free glass fiber, 30 weight parts of mineral powder, 5 weight parts of diphenylmethane diisocyanate compatibilizer, 0.5 weight parts of antioxidant 1010, and 0.4 weight parts of zinc stearate lubricant;

[0043] The polyoxymethylene is copolymerized oxymethylene, preferably copolymerized oxymethylene with medium viscosity and a melt flow rate of about 10 g / 10 min;

[0044] The polyurethane elastomer is a polyester polyurethane or a polyether polyurethane or a composite of the two, and has a Shore A hardness of 90 and a density of 1.19 g / cm3;

[0045] The alkali-free glass fiber is an alkali-free chopped glass fiber, preferably with a fiber length of 5.0 mm, a diameter of 15 μm, and an alkali-free chopped glass fiber treated with a coupling agent on the surface;

[0046] The mineral powder is one or a composite of talcum powder, glass micro beads or crushed glass fiber powder, and the mineral powder is 3000 mesh mineral powder.

[0047] The preparation method of the sodium sulfonate modified silicate is:

[0048] (1) Add pentaerythritol methyl silicate and propyl hexyl lactone to N,N-dimethylformamide solvent, mix well, add sodium hydroxide catalyst, wherein the mass ratio of pentaerythritol methyl silicate, propyl hexyl lactone and sodium hydroxide catalyst is 1:1.4:0.03, react at 70°C for 10 hours, and after the reaction, distill under reduced pressure, wash and dry to obtain intermediate 1;

[0049] (2) adding intermediate 1 and 2-methylene succinic anhydride to the reactor, stirring evenly, and continuing to add 4-dimethylaminopyridine catalyst, wherein the mass ratio of intermediate 1, 2-methylene succinic anhydride and 4-dimethylaminopyridine catalyst is 1.5:1:0.02, controlling the temperature between 80° C., reacting for 4 hours, filtering after completion, washing and drying to obtain intermediate 2;

[0050] (3) adding intermediate 2 to toluene solvent, stirring and dispersing, and then adding 4-dimethylaminophenol and p-toluenesulfonic acid catalyst thereto, wherein the mass ratio of intermediate 2, 4-dimethylaminophenol, and p-toluenesulfonic acid catalyst is 1.4:1:0.04, heating to 115° C., reacting for 10 hours, and after the reaction is completed, distilling under reduced pressure to obtain intermediate 3;

[0051] (4) dissolving the intermediate 3 and 1,3-propane sultone in a 1,4-dioxane solvent, wherein the mass ratio of the intermediate 3 to 1,3-propane sultone is 1:2.3, then dropping a 5% sodium hydroxide solution, heating to 85° C. to react for 10 h, and after the reaction, concentrating under reduced pressure to remove the solvent, and the crude product is recrystallized in ethanol to obtain a sodium sulfonate modified silicate;

[0052] (5) adding polyoxymethylene, sodium sulfonate modified silicate, polyurethane elastomer, mineral powder, diphenylmethane diisocyanate compatibilizer, antioxidant 1010, and zinc stearate lubricant into a high-speed mixer in sequence, stirring for 10 minutes to obtain a mixture;

[0053] (6) Extrusion granulation: The premix in S1 is fed into the feed hopper of a twin-screw extruder, and alkali-free glass fiber is added from the side feed of the fifth section for melt extrusion to obtain a molten low-floating fiber, rigidity and toughness balanced polyoxymethylene composite material; after traction, water cooling, blow drying, pelletizing and collection, a solid granular low-floating fiber, rigidity and toughness balanced polyoxymethylene composite material is finally obtained; wherein the extruder is a co-rotating meshing twin-screw extruder with a length-to-diameter ratio of 40:50:1, and the temperature control of each zone of the extruder is: 180°C for zones 1 to 3, 190°C for zones 4 to 10, 195°C for the head, 500rpm for the main engine speed, 30rpm for the main feeding frequency, 10rpm for the side feeding frequency, and 0MPa for the vacuum degree.

[0054] Example 3

[0055] A low-floating fiber rigid-toughness balanced polyoxymethylene composite material comprises the following weight components: 70 weight parts of polyoxymethylene, 12 weight parts of sodium sulfonate modified silicate, 15 weight parts of polyurethane elastomer, 20 weight parts of alkali-free glass fiber, 20 weight parts of mineral powder, 3 weight parts of diphenylmethane diisocyanate compatibilizer, 0.3 weight parts of antioxidant 1010, and 0.2 weight parts of zinc stearate lubricant;

[0056] The polyoxymethylene is copolymerized oxymethylene, preferably copolymerized oxymethylene with medium viscosity and a melt flow rate of about 10 g / 10 min;

[0057] The polyurethane elastomer is a polyester polyurethane or a polyether polyurethane or a composite of the two, and has a Shore A hardness of 85 and a density of 1.19 g / cm3;

[0058] The alkali-free glass fiber is an alkali-free chopped glass fiber, preferably with a fiber length of 4.0 mm, a diameter of 12 μm, and an alkali-free chopped glass fiber treated with a coupling agent on the surface;

[0059] The mineral powder is one or a combination of talcum powder, glass micro beads or crushed glass fiber powder, and the mineral powder is 2500 mesh mineral powder.

[0060] Preferably, the preparation method of the sodium sulfonate modified silicate is:

[0061] (1) Add pentaerythritol methyl silicate and propyl hexyl lactone to N,N-dimethylformamide solvent, mix well, add sodium hydroxide catalyst, wherein the mass ratio of pentaerythritol methyl silicate, propyl hexyl lactone and sodium hydroxide catalyst is 1:1.3:0.025, react at 65°C for 9 hours, and after the reaction, distill under reduced pressure, wash and dry to obtain intermediate 1;

[0062] (2) adding intermediate 1 and 2-methylene succinic anhydride to the reactor, stirring evenly, and continuing to add 4-dimethylaminopyridine catalyst, wherein the mass ratio of intermediate 1, 2-methylene succinic anhydride and 4-dimethylaminopyridine catalyst is 1.4:1:0.015, controlling the temperature between 65°C, reacting for 3h, filtering after completion, washing and drying to obtain intermediate 2;

[0063] (3) adding intermediate 2 to toluene solvent, stirring and dispersing, and then adding 4-dimethylaminophenol and p-toluenesulfonic acid catalyst thereto, wherein the mass ratio of intermediate 2, 4-dimethylaminophenol and p-toluenesulfonic acid catalyst is 1.3:1:0.03, heating to 110° C., reacting for 8 hours, and after the reaction is completed, distilling under reduced pressure to obtain intermediate 3;

[0064] (4) dissolving the intermediate 3 and 1,3-propane sultone in a 1,4-dioxane solvent, wherein the mass ratio of the intermediate 3 to 1,3-propane sultone is 1:2.2, then dropping a 4% sodium hydroxide solution, heating to 72° C. for reaction for 8 h, and after the reaction, concentrating under reduced pressure to remove the solvent, and the crude product is recrystallized in ethanol to obtain a sodium sulfonate modified silicate;

[0065] (5) adding polyoxymethylene, sodium sulfonate modified silicate, polyurethane elastomer, mineral powder, diphenylmethane diisocyanate compatibilizer, antioxidant 1010, and zinc stearate lubricant into a high-speed mixer in sequence, stirring for 7 minutes to obtain a mixture;

[0066] (6) Extrusion granulation: The premix in S1 is fed into the feed hopper of a twin-screw extruder, and alkali-free glass fiber is added from the side feed of the fifth section for melt extrusion to obtain a molten low-floating fiber rigidity and toughness balanced polyoxymethylene composite material; after traction, water cooling, blow drying, pelletizing and collection, a solid granular low-floating fiber rigidity and toughness balanced polyoxymethylene composite material is finally obtained; wherein the extruder is a co-rotating meshing twin-screw extruder with a length-to-diameter ratio of 40:25:1, and the temperature control of each zone of the extruder is: 160°C for zones 1 to 3, 185°C for zones 4 to 10, 192°C for the head, 350rpm for the main engine speed, 20rpm for the main feeding frequency, 7rpm for the side feeding frequency, and -0.04MPa for the vacuum degree.

[0067] Comparative Example 1

[0068] This comparative example is different from Example 3 in that no sodium sulfonate-modified silicate is added.

[0069] Use an oxygen index tester to test the oxygen index of the material.

[0070] The combustion level of the material is tested using a horizontal vertical combustion tester.

[0071] Table 1: Flame retardancy tests.

[0072] project Oxygen index (%) UL-94 Example 1 29 V-0 Example 2 30 V-0 Example 3 31 V-0 Comparative Example 1 22 V-1

[0073] It can be seen from Table 1 that Examples 1-3 of the present invention have better flame retardant effects than Comparative Example 1.

[0074] The materials prepared in Examples 1-3 and Comparative Example 11 were injection molded into specimens and tested according to the following standards: tensile strength test was carried out according to ISO 527-1 / -2; flexural modulus test was carried out according to ISO 178; notched impact strength test was carried out according to ISO 179-1 / 1eA; the floating fiber condition of the specimen was visually judged.

[0075] The test results are shown in Table 2 below.

[0076] Table 2: Summary of test results of sample material properties of Examples 1-3 and Comparative Example 1

[0077]

[0078] It can be seen from Table 2 that Examples 1-3 of the present invention have better mechanical properties than Comparative Example 1.

[0079] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A low-floating fiber rigidity-toughness balanced polyoxymethylene composite material, characterized in that: The invention comprises the following components by weight: 50-90 parts by weight of polyoxymethylene, 8-15 parts by weight of sodium sulfonate modified silicate, 5-20 parts by weight of polyurethane elastomer, 10-30 parts by weight of alkali-free glass fiber, 10-30 parts by weight of mineral powder, 1-5 parts by weight of diphenylmethane diisocyanate compatibilizer, 0.1-0.5 parts by weight of antioxidant 1010, and 0.1-0.4 parts by weight of zinc stearate lubricant; The polyoxymethylene is copolymerized oxymethylene, preferably copolymerized oxymethylene with medium viscosity and a melt flow rate of about 10 g / 10 min; The polyurethane elastomer is a polyester polyurethane or a polyether polyurethane or a composite of the two, with a Shore A hardness of 80-90 and a density of 1.19 g / cm3; The alkali-free glass fiber is an alkali-free chopped glass fiber, preferably with a fiber length of 3.0-5.0 mm, a diameter of 10-15 μm, and an alkali-free chopped glass fiber treated with a coupling agent on the surface; The mineral powder is one or a combination of talcum powder, glass micro beads or crushed glass fiber powder, and the mineral powder is 2000-3000 mesh mineral powder.

2. The low-floating fiber rigidity-toughness balanced polyoxymethylene composite material according to claim 1, characterized in that: The preparation method of the sodium sulfonate modified silicate is: (1) Add pentaerythritol methyl silicate and propyl caprolactone to N,N-dimethylformamide solvent, mix well, add sodium hydroxide catalyst, react at 60-70° C. for 7-10 hours, and after the reaction, distill under reduced pressure, wash, and dry to obtain intermediate 1; (2) Add intermediate 1 and 2-methylene succinic anhydride to the reactor, stir evenly, continue to add 4-dimethylaminopyridine catalyst, control the temperature between 50-80° C., react for 1.5-4 hours, filter, wash and dry after completion to obtain intermediate 2; (3) adding intermediate 2 to toluene solvent, stirring and dispersing, then adding 4-dimethylaminophenol and p-toluenesulfonic acid catalyst, heating to 105-115° C., reacting for 7-10 hours, and after the reaction is completed, distilling under reduced pressure to obtain intermediate 3; (4) The intermediate 3 and 1,3-propane sultone are dissolved in a 1,4-dioxane solvent, and then a sodium hydroxide solution with a mass fraction of 3-5% is added dropwise, and the temperature is raised to 60-85° C. for reaction. After the reaction, the solvent is removed by concentration under reduced pressure, and the crude product is recrystallized in ethanol to obtain a sodium sulfonate modified silicate.

3. The low-floating fiber-rigidity-balanced polyoxymethylene composite material according to claim 2, characterized in that: The mass ratio of pentaerythritol methyl silicate, propyl caprolactone and sodium hydroxide catalyst in (1) is 1:1.2-1.4:0.02-0.

03.

4. The low-floating fiber-rigidity-balanced polyoxymethylene composite material according to claim 2, characterized in that: The mass ratio of the intermediate 1, 2-methylenesuccinic anhydride and 4-dimethylaminopyridine catalyst in (2) is 1.3-1.5:1:0.01-0.

02.

5. The low-floating fiber-rigidity-balanced polyoxymethylene composite material according to claim 2, characterized in that: The mass ratio of the intermediate 2,4-dimethylaminophenol to the p-toluenesulfonic acid catalyst in (3) is 1.1-1.4:1:0.02-0.

04.

6. The low-floating fiber-rigidity-balanced polyoxymethylene composite material according to claim 2, characterized in that: The mass ratio of the intermediate 3 to 1,3-propane sultone in (4) is 1:2.1-2.

3.

7. The low-floating fiber-rigidity-balanced polyoxymethylene composite material according to claim 2, characterized in that: The reaction time in (4) is 6-10h.

8. A method for preparing the low-floating fiber-rigidity-toughness balanced polyoxymethylene composite material according to any one of claims 1 to 7, characterized in that: The preparation method of the low-floating fiber rigidity-toughness balanced polyoxymethylene composite material is: S1, adding polyoxymethylene, sodium sulfonate modified silicate, polyurethane elastomer, mineral powder, diphenylmethane diisocyanate compatibilizer, antioxidant 1010, and zinc stearate lubricant into a high-speed mixer in sequence, stirring for 5-10 minutes to obtain a mixture; S2, extrusion granulation: the premix in S1 is put into the feeding hopper of the twin-screw extruder, and the alkali-free glass fiber is added from the side feeding of the fifth section for melt extrusion to obtain a molten low-floating fiber rigidity and toughness balanced polyoxymethylene composite material; after traction, water cooling, blow drying, pelletizing and collection, a solid granular low-floating fiber rigidity and toughness balanced polyoxymethylene composite material is finally obtained; wherein the extruder is a co-rotating meshing twin-screw extruder, and the aspect ratio is between 40:1-50:1, and the temperature control of each zone of the extruder is: 150-180℃ for zones 1 to 3, 180-190℃ for zones 4 to 10, 190-195℃ for the head, 300-500rpm for the main engine speed, 10-30rpm for the main feeding frequency, 5-10rpm for the side feeding frequency, and -0.08-0MPa for the vacuum degree.

Citation Information

Patent Citations

  • Enhancing toughening polyoxymethylene composition and method for producing the same

    CN101130621A

  • Toughened polyoxymethylene blended modifier and preparation method thereof

    CN101921453A